Roof water harvesting for domestic water security: who gains and who loses? - Kumar, M. Dinesh (2004)
Roof water harvesting is being widely promoted as a panacea for the growing drinking water crisis in India and many underdeveloped and developing countries. This article analyzes the scope, physical feasibility, and economic viability of roof water harvesting systems across classes and under different physical and socioeconomic situations. This article argues that roof water harvesting systems (RWHS) are not alternative to public systems in urban and rural areas of regions receiving low rainfall. Hydrological opportunities for RWHS are very poor in urban and rural areas. The systems offer very little scope in ensuring domestic water security for urban housing stocks of low- and middle-income groups. At the same time, they offer tremendous potential for independent bungalows having large roof area. However, their physical feasibility is very poor in urban areas. Their economic viability as a supplementary source of domestic water supply seems to be poor in urban areas, when compared to augmenting the supplies from the existing public systems. The incredibly low rates charged for domestic supplies by urban water utilities and government subsidies for RWHS would only lead to the urban elite increasing their access to water supplies, while the burden on water utilities would remain unchanged. This will lead to greater inequities in access to water supplies. At the same time, in rural areas with dispersed populations and hilly areas, RWHS may be economically viable as a supplementary source to already existing public water supply schemes. But as its impacts are not likely to be uniform across classes, government subsidies are not desirable. In hilly regions receiving high rainfalls, government investment for community water supply schemes could be replaced by heavy subsidies for installation of RWHS.